Comparison of retinal vessel diameter measurements from swept-source OCT angiography and adaptive optics ophthalmoscope - Yao, Xinwen; Ke, Mengyuan; Ho, Yijie; Lin, Emily; Wong, Damon W K; Tan, Bingyao; Schmetterer, Leopold; Chua, Jacqueline (British journal of ophthalmology, 2021)
Background/imsTo compare the retinal vessel diameter measurements obtained from the swept-source optical coherence tomography angiography (OCTA; Plex Elite 9000, Carl Zeiss Meditec, USA) and adaptive optics ophthalmoscope (AOO; RTX1, Imagine Eyes, France).MethodsFifteen healthy subjects, 67% women, mean age (SD) 30.87 (6.19) years, were imaged using OCTA and AOO by a single experienced operator on the same day. Each eye was scanned using two OCTA protocols (3×3 mm2 and 9×9 mm2) and two to five AOO scans (1.2×1.2 mm2). The OCTA and AOO scans were scaled to the same pixel resolution. Two independent graders measured the vessel diameter at the same location on the region-of-interest in the three coregistered scans. Differences in vessel diameter measurements between the scans were assessed.ResultsThe inter-rater agreement was excellent for vessel diameter measurement in both OCTA protocols (ICC=0.92) and AOO (ICC=0.98). The measured vessel diameter was widest from the OCTA 3×3 mm2 (55.2±16.3 µm), followed by OCTA 9×9 mm2 (54.7±14.3 µm) and narrowest by the AOO (50.5±15.6 µm; p<0.001). Measurements obtained from both OCTA protocols were significantly wider than the AOO scan (OCTA 3×3 mm2: mean difference Δ=4.7 µm, p<0.001; OCTA 9×9 mm2: Δ=4.2 µm, p<0.001). For vessels >45 µm, it appeared to be larger in OCTA 3×3 mm2 scan than the 9×9 mm2 scan (Δ=1.9 µm; p=0.005), while vessels <45 µm appeared smaller in OCTA 3×3 mm2 scan (Δ=−1.3 µm; p=0.009)ConclusionsThe diameter of retinal vessels measured from OCTA scans were generally wider than that obtained from AOO scans. Different OCTA scan protocols may affect the vessel diameter measurements. This needs to be considered when OCTA measures such as vessel density are calculated.